Peningkatan Hasil Pembelajaran Menggunakan Model Kooperatif Tipe Make a Match SD - Cahyani, Regika Rezi; Arwin, Arwin; Lubis, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The purpose of this study was to describe the improvement of integrated thematic learning outcomes using the Cooperative type Make A Match model in class V of SDN 33 Pasaman, West Pasaman Regency. The research subjects were teachers (practitioners) and 23 students. The place of research is SDN 33 Pasaman, West Pasaman Regency. The results showed an increase in: a) the score oh the lesson plan in cycle I was 86.36% (A-), cycle II 95.45% (A); b) observation of aspects of teacher cycle I 83.32% (B+), cycle II 94.44% (A); c) aspects of observation of the first cycle I students 83.32% (B+) and the second cycle II 94.44% (A); d) learning outcomes in the first cycle I 74.7% (B); and the second cycle II 87.1% (A-). Keywords: integrated thematic learning, Cooperative type Make A Match model model